Immigration and careers of European workers: Effects and the role of policies - Cristina Cattaneo; Carlo V. Fiorio; Giovanni Peri (IZA Journal of European Labor Studies, 2013)
In this paper we analyze the response of career, employment and wage of native Europeans to immigration. We then ask how individual country's policies affect these responses. We use data on 11 EU countries, over the period 1995-2001. We also use the 1991 distribution of immigrants by nationality across European labor markets to construct a version of the enclave-based instrument to proxy for the flow of immigrants, that is exogenous to local demand shocks. We find that native Europeans are more likely to upgrade to more skilled and better paid occupations, when a larger number of immigrants enter their labor market. We find no evidence of an increased likelihood of non-employment or geographical mobility. We find that more flexible labor markets in a country are a key factor to have employment upgrading in response to immigration.
Keywords: J61; O15; 330; Immigrants; Europe; Occupation upgrading; Mobility; Labor market policies